Protein Tyrosine Phosphatases in Hypothalamic Insulin and Leptin Signaling. (October 2015) - Zhang, Zhong-Yin; Dodd, Garron T.; Tiganis, Tony
Abstract : The hypothalamus is critical to the coordination of energy balance and glucose homeostasis. It responds to peripheral factors, such as insulin and leptin, that convey to the brain the degree of adiposity and the metabolic status of the organism. The development of leptin and insulin resistance in hypothalamic neurons appears to have a key role in the exacerbation of diet-induced obesity. In rodents, this has been attributed partly to the increased expression of the tyrosine phosphatases Protein Tyrosine Phosphatase 1B (PTP1B) and T cell protein tyrosine phosphatase (TCPTP), which attenuate leptin and insulin signaling. Deficiencies in PTP1B and TCPTP in the brain, or specific neurons, promote insulin and leptin signaling and prevent diet-induced obesity, type 2 diabetes mellitus (T2DM), and fatty liver disease. Although targeting phosphatases and hypothalamic circuits remains challenging, recent advances indicate that such hurdles might be overcome. Here, we focus on the roles of PTP1B and TCPTP in insulin and leptin signaling and explore their potential as therapeutic targets. Trends: PTP1B and TCPTP act in concert to attenuate leptin and insulin signaling in hypothalamic neurons. Combined deficiencies in PTP1B and TCPTP in POMC neurons in the hypothalamus promote the browning of white fat to increase energy expenditure and combat the development of diet-induced obesity, glucose intolerance, and fatty liver disease. Inhibiting PTP1B and TCPTP in the brain may prevent diet-induced obesity.